International experience and intercultural sensitivity of American and VietNamese high school students - Đồng, Thị Thùy Linh (2020)
In today’s international setting, students have been dramatically increasing their exposure to different cultures worldwide. Following this trend, American students thus can be seen studying in Vietnam and vice versa. These students are in force of developing intercultural sensitivity so as to avoid culture shocks and survive successfully in culturally-distinct environment. This study then aims at exploring this under researched area of international experience and intercultural sensibility of American and Vietnamese high school students. With triangulation method, the study was divided into two phases. In the first phase, survey questionnaires were employed to study 100 students’ intercultural sensitivity in regard to their interaction engagement, respect for cultural differences, interaction enjoyment, interaction attentiveness, and interaction confidence. In the second phase, two classes selected from two sets of sample were observed with highly structured checklists. The data collected from both phases formulated to answer the two key research questions. A brief summary of the findings reveals that (1) American students with their wide range of international experience reached a higher level of interaction engagement, enjoyment and attentiveness in comparison with their Vietnamese fellow students (2) Concerning students’ self-reports on their intercultural sensitivity development over the period of American – Vietnamese interaction, the two current programs are perceived to expand a limited influence on their intercultural sensitivity (3) Frequency of foreign language in class plays a deciding role in the development of students’ intercultural sensitivity. At last, this paper concludes with some implication and application which are hoped to be found helpful to some extent for students, teachers, and researchers who are also interested in this topic.